Bahasa Inggris - Novrianti, Bolivani; Soni Mirizon; Eryansyah (Jurnal Pendidikan Indonesia, 2024)
The identity transition of four prospective professional teachers while undergoing a professional development program is essential to consider. This research aims to understand the dynamics and processes that allow professional identities to develop and change. This research uses qualitative research and Schlossberg's transition model as a framework. The research participants were four prospective teachers from the Teacher Professional Education program. Data collection was carried out using the narrative inquiry method. The data analysis technique uses qualitative descriptive analysis. This study found that identity trajectories from the pre-transition period contributed to their current identity transition. Their previous change in identity was because teaching is an honorable profession with other perceived benefits, such as economic and cultural capital. In this program, prospective teachers said there was a transformation in their professional experience. The study emphasizes the importance of continuing education for prospective teachers to become professional teachers. Teacher education plays a vital role in ensuring that teachers have a strong foundation in the theory and practice of education. Qualified teachers are critical in providing effective and quality education to students, so teacher education is essential to the education system.